An investigation of debt management practices as a perfomance measure: a case of Harare polytechnic college - Chirenga, Brenda (Midlands State University, 2018)
This research sought to investigate the debt management practices as a performance measure at Harare Polytechnic College. The college under study was facing liquidity problems due to the ineffective debt management methods employed. There has been an increase in debtors’ balances from 2014 to 2016 due to the college failing to recover debts from the students who owed the college and this affected the college financially. The researcher used the qualitative approach to carry out the study. A census approach was used since the target population was very small. The researcher used questionnaires and interviews to collect data for the research. The major findings from the research were that the current debt management were ineffective leading to a decline in performance. The research revealed that the current debt management system is facing challenges leading to its failure to improve liquidity of the college. The research also revealed that there are other practices that can be employed to improve the liquidity. The researcher recommended that the college offer realistic payment plans to improve payment by the debtors. The college should update the current system they are using for debt management so as to enable them to keep relevant information about debtors reflecting correct amounts. Employees should be continuously trained so that they possess the adequate skills for debt management. The college should ensure that it has a single department for all its collections and this makes the management of debt more effective.